Online Assessment Effect in EFL Classroom: An Investigation on Students and Teachers’ Perceptions - Fitriyah, Ima; Jannah, Miftahul (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
The teaching and learning process changed into an online during the COVID-19 outbreak, and thus online evaluation became a requirement. This research examines the positive and negative effects of online assessment on students’ learning behaviour and how teachers prepare their teaching. This case study research included the result of questionnaire from thirty IC students followed by interview with three EFL teachers in the Intensive English Course (IC) program and six IC program students in one of Islamic University in Kediri. The small survey indicated that students have positive attitude toward the administration of online assessment. Furthermore, the outcomes of open-ended interviews showed that there were four themes for beneficial effects, including enhancing flexibility in assessment, improving evaluation versatility, building teachers and students’ awareness of preparing evaluation and cultivating students’ autonomous learning abilities. On the other hand, three themes for negative effects emerged from the online assessment, including complication of evaluation administration, reduced interaction between teachers and students, and anxiety in English test. The effects emerge from how teachers and students view the drawbacks of the online assessment itself. Positive effects lead to students’ learning better are caused by lesson taken from conducting the test; however, the negatives should be treated as challenges that will improve the teaching and learning. Finally, both teachers and students are ready to face online assessment in the future.